Reenactment: Tournaments, Chronicles and Visual History. Issue 1 (2nd January 2019) - Logemann, Cornelia
ABSTRACT: In the illustration of chronicle texts in the Western Middle Ages, the question often arises of how the reading of a manuscript changes when illuminations influence the reader's perception. For in addition to a direct connection to the surrounding text in a manuscript, images also form their own reference system. Recurring pictorial formulas are therefore not only due to the serial production of illuminated manuscripts, but are also addressed to the imagination of the viewer. Tournament images, especially, show how a visual topos can open completely new references and form a new visual history. In addition to a few historical sources, tournaments were extensively described, especially in courtly literature, and the visual surface and splendour of these events in the Arthurian world seemed to fascinate audiences on all levels. Even in late medieval French chronicles like those of Jean Froissart, images and imaginings of tournaments turn out to be a window onto a mythical ideal past. The ideal chivalric virtues are invoked in these pictures, in which the cultural practice of the late Middle Ages on the one hand and different genres on the other overlap.